2018
DOI: 10.1029/2018jc014348
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Air‐Sea Momentum Flux Variability Across the Inner Shelf

Abstract: Over the open ocean, the aerodynamic drag coefficient is typically well predicted; however, the impact depth‐limited processes have on the drag remains underexplored. A case study is presented here where winds, waves, and currents were simultaneously observed from a mobile platform that repeatedly transected the inner shelf of Monterey Bay, CA. Eddy covariance‐derived drag coefficients were compared to several bulk parameterizations, including all of the roughness variations of COARE 3.5 and two explicitly dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…During CASPER‐West, the sea state was persistently mixed, with three directionally distinct energy bands identifiable throughout much of the experiment: E s , E m , and E w , where E is the surface elevation variance density and subscripts represent the low frequency swell ( s ), mid‐frequency swell ( m ), and local windsea bands ( w ), respectively. The three bands were separated by f s (an arbitrary limit between E s and E m set to 0.08333) and f c , defined as (Ortiz‐Suslow et al., 2018): fc=g2.4πUcos(ψDp), where g is gravitational acceleration (9.81 ms −1 ), U is the local mean wind speed, ψ is the local mean wind direction, and D p is the direction of the spectral wave peak. If f c < 0.125, then the sea state was assumed to resemble a bi‐modal distribution with distinct swell ( E s ) and windsea ( E w ) bands only, that is, E m = 0.…”
Section: Methodology and Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…During CASPER‐West, the sea state was persistently mixed, with three directionally distinct energy bands identifiable throughout much of the experiment: E s , E m , and E w , where E is the surface elevation variance density and subscripts represent the low frequency swell ( s ), mid‐frequency swell ( m ), and local windsea bands ( w ), respectively. The three bands were separated by f s (an arbitrary limit between E s and E m set to 0.08333) and f c , defined as (Ortiz‐Suslow et al., 2018): fc=g2.4πUcos(ψDp), where g is gravitational acceleration (9.81 ms −1 ), U is the local mean wind speed, ψ is the local mean wind direction, and D p is the direction of the spectral wave peak. If f c < 0.125, then the sea state was assumed to resemble a bi‐modal distribution with distinct swell ( E s ) and windsea ( E w ) bands only, that is, E m = 0.…”
Section: Methodology and Approachmentioning
confidence: 99%
“…Several field studies have shown that the relative direction between the wind and dominant waves can help explain unexpected changes in wind stress and other parameters with time and/or space (Grachev et al 2003;Ortiz-Suslow et al 2018, 2015Shabani et al 2014;Zhang, Drennan, Haus, & Graber 2009). To account for this here, the relative angle between the wind direction (ψ) and mid-frequency swell peak wave directions (D pm ) was examined.…”
Section: Definition Of Surface Wave Spectral Energy Bandsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, COARE does not isolate the contribution or impact of SF to the fluxes, and therefore doing a comparison between EC and bulk techniques may highlight the separate impact SF have on the air‐sea exchange. This method of testing against bulk parameterizations has been used to assess the impact of nonresolved processes in previous works, for example, over complex nearshore regions (Ortiz‐Suslow et al, , ).…”
Section: Analysis Methodsmentioning
confidence: 99%
“…They further observed the stress vector deviation to be correlated with the horizontal current shear, and concluded that open ocean parameterizations underestimate the drag coefficient by a factor of 2.6. Recently, Ortiz-Suslow et al [10] observed a shift from swell-to current-dominated wind stress veering at a distance of 2 km off the coast in Monterey Bay, California. They reported a relationship between the wind stress veering and the alongshore surface current variance, within 2 km off the coast.…”
Section: Introductionmentioning
confidence: 99%